Effects of pressure and noise on the stability of photoacoustic signals of trace gas components - Zhu, Zhizhen; Luo, Jing; Liu, Jiaxiang; Fang, Yonghua (International Journal of Agricultural and Biological Engineering, 2020)
In essence, photoacoustic spectroscopy (PAS) technology is based on the thermal effect of gas infrared absorption and the acoustic theory of photoacoustic (PA) cell. PAS technology has a good application effect on environmental monitoring in agriculture. In this study, carbon monoxide and sulfur dioxide were used as examples to explain the potential application of PAS technology and analyze the influence mechanism of pressure and noise on the PA signal. The relationship between PA signal amplitude and the concentration of gas was determined by calibration. The pressure and noise characteristics were experimentally studied, and the relationship between the PA signal and pressure & noise was obtained. The theoretical analysis and experimental results not only provided a basis for further correction of the influence of pressure, noise and other factors on PA signal but also provided technical support for improving the field application of trace gas non-resonance PA detection device for environmental monitoring in agriculture. Keywords: photoacoustic spectroscopy, environmental monitoring in agriculture, trace gas, pressure, noise DOI: 10.25165/j.ijabe.20201305.5749 Citation: Zhu Z Z, Luo J, Liu J X, Fang Y H. Effects of pressure and noise on the stability of photoacoustic signals of trace gas components. Int J Agric & Biol Eng, 2020; 13(5): 187–193.